Flammability properties of paper coated with poly (methylenephosphine), an organophosphorus polymer. (20th August 2014) - Priegert, Andrew M.; Siu, Paul W.; Hu, Thomas Q.; Gates, Derek P.
Summary: The flame retardant properties of paper coated with either poly(methylenephosphine) (PMP ) or poly(methylenephosphine oxide) (PMP‐O ) are evaluated. Paper sheets made from thermomechanical pulp were coated withPMP ( M n  = 27, 000 g mol −1, polydispersity index (PDI) = 1.47), PMP‐O ( M n  = 30, 000 g mol −1, PDI = 1.24), or monobasic ammonium phosphate (MAP) to achieve an approximate loading of 0.8 mmol P/g paper. Thermal stability studies by thermogravimetric analysis show that the paper degrades in two main stages, with the second thermo‐oxidative stage having a slower rate of degradation for paper treated with flame retardants. The flame retardancy of the sheets was evaluated by Technical Association of Pulp and Paper Industry Standard Method T461 cm‐00 and by limiting oxygen index (LOI) according to ASTM D2863. After leaching with water, samples coated withPMP orPMP‐O show no loss of flame retardancy, while those coated with MAP lose all flame retardancy. The LOI of paper coated withPMP (23.1%) orPMP‐O (25.9%) is higher than those of uncoated paper (19.6%), but lower than MAP‐coated paper (34.7%). Analysis of the char provided evidence that the flame retardant mechanism ofPMP andPMP‐O involves the formation of phosphorus oxides and acids. Copyright © 2014 John Wiley & Sons, Ltd.